2013
DOI: 10.1039/c3cp50942g
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–graphene composites with exposed {001} facets produced by a one-pot solvothermal approach for high performance photocatalyst

Abstract: TiO2-graphene (TOG) composites with exposed TiO2 {001} facets were prepared by a solvothermal approach without any addition of surfactants or capping agents, only using titanium isopropoxide and graphene oxide ethanol suspension as the precursors. Graphene was covered uniformly and densely with anatase TiO2 nanoparticles, exposing the {001} facets. The X-ray photoelectron spectroscopy, photoluminescence spectroscopy and photocurrent measurements show the presence of electron transfer between TiO2 and graphene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 51 publications
1
52
0
Order By: Relevance
“…However, modified Hummer's method is the preparation method most frequently used for TiO 2 -graphene nanocomposites [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, modified Hummer's method is the preparation method most frequently used for TiO 2 -graphene nanocomposites [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorptivity measurements (Supporting Information Fig. S3) suggested that introduction of RGO could increase the adsorptivity of reactants because of pep conjugation between aromatic nitro organics and the aromatic regions of RGO [29], rather than negligible variations in surface area resulting from the low RGO content. This increased TiO 2 HS/RGO composite adsorptivity promotes the photocatalytic reduction of aromatic nitro organics on the photocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…Anderson et al reported that TiO 2 /thermally RGO composites showed superior photocatalytic activity for phenol degradation [27]. In general, electrons in TiO 2 /RGO composites transfer from TiO 2 to RGO through interfacial charge-transfers, leading to improved separation of electrons and holes [28,29]. This phenomenon reveals the potential use of TiO 2 /RGO composites for efficient photocatalytic selective reduction, which is strongly dependent on photogenerated electron transfer from semiconductors under light irradiation.…”
Section: Introductionmentioning
confidence: 93%
“…7c shows the C1s spectrum of sample (b). The peaks at 284.69 and 285.08 eV were assigned to C=C/C-H aromatic and C-C/C-H aliphatic, respectively [37,38]. The peak at 285.69 eV can be ascribed to the C-O-Ti bond [35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%